Experimental Study of the Electrical Resistivity of Glass-Carbon/Epoxy Hybrid Composites. Issue 3 (March 2014) - Liu, Xin; Wu, Zhanjun; Wang, Rongguo; Yan, Jia
The electrical resistivity of composite materials varies with the changing of structural parameters, and this feature could be used to improve their electromagnetic wave absorbing property. This work investigated the electrical resistivity of hybrid composites aiming at radar absorbing structures. The glass-carbon/epoxy hybrid composites with different structural parameters were prepared by filament winding machine. And the effects of hybrid style, hybrid ratio, curing pressure, fiber distribution and fiber orientation on electrical resistivity were tested. As the test results shown, firstly, the electrical resistivity of interlaminated hybrid composites is larger than that of intraply hybrid composite; secondly, the electrical resistivity of hybrid composite is inversely proportional to the content of carbon fiber; thirdly, the electrical resistivity of hybrid composite with carbon fiber homogeneous distribution is larger than that of hybrid composite with inhomogeneous distribution; finally the electrical resistivity of hybrid composite would decrease with the curing pressure increasing. Interestingly there are similar rules in the vertical and parallel direction of the fibers. These results are helpful to control and adjust the electrical resistivity of glass-carbon/epoxy hybrid composites.